2019
DOI: 10.1038/s41699-019-0124-4
|View full text |Cite
|
Sign up to set email alerts
|

Far-UV photoluminescence microscope for impurity domain in hexagonal-boron-nitride single crystals by high-pressure, high-temperature synthesis

Abstract: Hexagonal-boron-nitride single crystals grown by high-pressure, high-temperature (HPHT) synthesis are commonly used as the insulated substrate dielectric for two-dimensional (2D) atomic-layered materials like graphene and transition metal dichalcogenides (TMDs) to improve the flatness of the 2D materials atomically without disturbing the 2D electronic characteristics. However, HPHT single crystals often contain impure regions, which can hold subtle clues in regard to the 2D atomic-layered materials for new dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…As a matter of fact, the regime of very few numbers of hBN layers remains unexplored by means of optical spectroscopy in the deep-UV. In this context, the recent achievements in the development of spatially-resolved PL setups in this spectral domain are full of promises [11,20,21]. One example is shown in Figure 4 (corresponding to Ref.…”
Section: Towards Few-layer Hbn Crystalsmentioning
confidence: 99%
“…As a matter of fact, the regime of very few numbers of hBN layers remains unexplored by means of optical spectroscopy in the deep-UV. In this context, the recent achievements in the development of spatially-resolved PL setups in this spectral domain are full of promises [11,20,21]. One example is shown in Figure 4 (corresponding to Ref.…”
Section: Towards Few-layer Hbn Crystalsmentioning
confidence: 99%
“…It is followed by a series of 148 meV-split global repeats of the fine structure splitting observed at the scale of the four different phonon replicas TA, LA, TO and LO, which we discussed above. The number of defects that give the final density of states in Fermi's golden rule gives the intensity of the photoluminescence in this energy range, and it can be inhibited in regions free from defects [106,110]. Defects are appropriately selected by K-K′ intervalley scattering of carriers in hand and by emission of zone-edge TO(K) optical phonons, which is a selection rule process dictated by group theory arguments [111].…”
Section: Excitons In Hbn 51 Deep Ultraviolet Photoluminescence and Ementioning
confidence: 99%
“…Using a more spatially focused beam than a laser one, that is to say by doing cathodoluminescence measurements, it is possible to excite regions of the crystal free from defects. Then the fluorescence is freed from contributions of such defects [17,110,132]. However, cathodoluminescence measurements failed to detect fluorescence for thicknesses smaller than six monolayers [133].…”
Section: From Epilayers To the Monolayer From Indirect To Direct Bandmentioning
confidence: 99%
“…Thus, the development of novel growth techniques is highly desirable. Recently, a few studies reported the utilization of the highpressure and high-temperature (HPHT) growth method to grow the two-dimensional layered single crystals (Watanabe and Taniguchi, 2019). The high temperature and high pressure facilitate the crystallization and growth of crystals remarkably, which has provided an alternative and effective way toward the controlled growth of single crystals.…”
Section: Introductionmentioning
confidence: 99%